Cumulative Social Risk and Child Screen Use: The Role of Child Temperament. (13th August 2021) - McArthur, Brae Anne; Hentges, Rochelle; Christakis, Dimitri A; McDonald, Sheila; Tough, Suzanne; Madigan, Sheri
Abstract: Objectives: It is critical to understand what children, and in which context, are at risk for high levels of screen use. This study examines whether child temperament interacts with cumulative social risk to predict young children's screen use and if the results are consistent with differential susceptibility or diathesis-stress models. Methods: Data from 1, 992 families in Calgary, Alberta (81% White; 47% female; 94% >$40, 000 income) from the All Our Families cohort were included. Mothers reported on cumulative social risk (e.g., low income and education, maternal depression) at <25 weeks of gestation, child's temperament at 36 months of age (surgency/extraversion, negative affectivity, effortful control), and child's screen use (hours/day) at 60 months of age. Along with socio-demographic factors, baseline levels of screen use were included as covariates. Results: Children high in surgency (i.e., high-intensity pleasure, impulsivity) had greater screen use than children low in surgency as social risk exposure increased. In line with differential susceptibility, children high in surgency also had less screen use than children low in surgency in contexts of low social risk. Children with heightened negative affectivity (i.e., frequent expressions of fear/frustration) had greater screen use as social risk increased, supporting a diathesis-stress model. Conclusions: Young children predisposed to high-intensity pleasure seeking and negative affectivity in environments characterized as high in social risk may be prone to greater durations of screen use. Findings suggest that an understanding of social risks and individual characteristics of the child should be considered when promoting healthy digital health habits.